Goats for meat, milk and fibre: A review - Rai, B; Singh, M K; Singh, S K (The Indian Journal of Animal Sciences, 2005)
Goat keeping has been a traditional activity in India and primary source of livelihood of people below poverty line. The total goat population in India was 123 million during 2003. There are 20 recognized goat breeds in India of varying potential producing meat, milk and fibre. Black Bengal, Barbari, Osmanabadi and Kannaiadu goat breeds are of high repute for meat quality and production. Jamunapari, Beetal, Jakhrana and Surti for milk, and Changthangi, Chegu and Gaddi for fibre/pashmina. The goat research was mostly conducted at institutional or organized farms under challenge feeding with small population size involving few breeds. However, improvement programmes for important goat breeds of various climatic zones of India was initiated during Fifth Five Year Plan in a planned manner under AICRP on goat. The main objective of this project was to improve meat, milk and fibre potential of native goat breeds through crossbreeding with exotic goats as well as through selective breeding. The crossbreeding with exotic breeds was discontinued due to poor reproductive performance and high mortality rate in higher grade crosses. Subsequently, the AICRP project was modified (8th and 9th Plan) with the aim to improve the production potential of native breeds through selective breeding in their respective home tract. The results accrued from this project are encouraging and improvement was recorded in meat and milk production (Barbari, Jamunapari, Sirohi, Black Bengal, Sangamneri etc.). Field studies conducted on Jakhrana, Zalawadi, Barbari, Black Bengal and Osmanabadi indicated that goats are primarly being raised under extensive management system. Lack of high potential and true to breed bucks is major threat for the dilution and low production. The research experiences on goats suggested that superior germ plasm in the farmer's flock may be identified and distributed for further improvement. Crossbreeding of native goats with exotic breeds is not suitable in Indian conditions. Selective breeding should be strictly practiced for improvement in meat, milk and fibre production. Up gradation of non-descript goats with improver breeds (Beetal, Jakhrana, Jamunapari and Barbari etc.) may be practiced under field conditions.